2015
DOI: 10.1016/j.bbr.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Gabaergic and opioid receptors mediate the facilitation of NaCl intake induced by α2-adrenergic activation in the lateral parabrachial nucleus

Abstract: Alpha2-adrenergic, gabaergic or opioidergic activation in the lateral parabrachial nucleus (LPBN) increases sodium intake. In the present study, we investigated the effects of single or combined blockade of opioidergic and gabaergic receptors in the LPBN on the increase of 0.3M NaCl intake induced by α2-adrenoceptor activation in the LPBN. Male Holtzman rats (n=5-9/group) with cannulas implanted bilaterally in the LPBN were treated with the diuretic furosemide (10 mg/kg b wt.) combined with low dose of the ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…Injections centered in the ventral lateral and external lateral portions, as well as in the Kölliker-Fuse nucleus observed in some rats were also considered as correctly placed in the LPBN. The sites of the injections in the present study were similar to those of previous studies that showed the effects of moxonidine injected into the LPBN on NaCl and water intake (Andrade et al, 2011(Andrade et al, , 2012(Andrade et al, , 2015 3.2. Experiment 1: Moxonidine injection into the LPBN: urinary sodium excretion and urinary volume in fluid-depleted rats Moxonidine injected bilaterally into the LPBN did not change urinary sodium excretion or urinary volume when compared to the LPBN vehicle injections in FURO + CAP treated rats that had no access to fluids.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Injections centered in the ventral lateral and external lateral portions, as well as in the Kölliker-Fuse nucleus observed in some rats were also considered as correctly placed in the LPBN. The sites of the injections in the present study were similar to those of previous studies that showed the effects of moxonidine injected into the LPBN on NaCl and water intake (Andrade et al, 2011(Andrade et al, , 2012(Andrade et al, , 2015 3.2. Experiment 1: Moxonidine injection into the LPBN: urinary sodium excretion and urinary volume in fluid-depleted rats Moxonidine injected bilaterally into the LPBN did not change urinary sodium excretion or urinary volume when compared to the LPBN vehicle injections in FURO + CAP treated rats that had no access to fluids.…”
Section: Discussionsupporting
confidence: 87%
“…Rats were anesthetized with ketamine (80 mg/kg of body weight) combined with xylazine (7 mg/kg of body weight) and placed in a stereotaxic instrument (Insight EFF 331, Insight Instruments, Ribeirão Preto, Brazil). The surgery for bilateral LPBN cannula placements is described in earlies studies from our lab (Andrade et al, 2004(Andrade et al, ., 2012(Andrade et al, , 2015.…”
Section: Lpbn Cannulasmentioning
confidence: 99%
“…It is not clear the reason for the different effects of methysergide or moxonidine into the LPBN on water intake in rats treated with aldosterone into the 4th V. Different studies have shown that the increase in water intake with methysergide injected into the LPBN when rats simultaneously ingest hypertonic NaCl is not consistent and only in part of the tests with methysergide into the LPBN water intake significantly increased in this condition (Menani et al, 1996(Menani et al, , 2000(Menani et al, , 2002De Luca et al, 2003). Although water intake increased in rats treated with moxonidine combined with high dose of aldosterone into the 4th V, the increase in water intake with moxonidine injected into the LPBN is also not consistent (Andrade et al, 2004(Andrade et al, , 2006(Andrade et al, , 2007(Andrade et al, , 2011(Andrade et al, , 2015, which suggests that rats are driven to ingest sodium in detriment to water when they receive methysergide or moxonidine into the LPBN, probably as a consequence of the strong preference for sodium in this condition. Chronic infusion of aldosterone into the 4th V also strongly increases hypertonic NaCl intake, without significant changes in water intake (Formenti et al, 2013), which confirms that the ingestion of significant amounts of hypertonic NaCl not necessarily causes increases in water intake if rats are motivated to ingest sodium.…”
Section: Discussionmentioning
confidence: 92%
“…Lesions of the CeA reduce daily sodium intake or that induced by ANG II or mineralocorticoids, suggesting that important facilitatory mechanisms for sodium intake are present in the CeA (Galaverna et al, 1992;Zardetto-Smith et al, 1994). Recent studies have also shown that the blockade of neuronal activity of the CeA with the GABAA agonist muscimol or the antagonism of the opioid receptors with naloxone abolished the increase of sodium intake in rats treated with FURO + CAP combined with the blockade of the LPBN inhibitory mechanisms, suggesting that the LPBN may inhibit CeA mechanisms that facilitate sodium intake (Andrade et al, 2015). It was also suggested that the CeA receives projections from the NTS and particularly from the HSD2 neurons of the NTS .…”
Section: Discussionmentioning
confidence: 99%
“…Different neurotransmitters and receptors present in the LPBN are involved in the control of water and NaCl intake. Some neurotransmitters/receptors like serotonin, cholecystokinin, corticotrophin release factor and glutamate in the LPBN activates the inhibitory mechanisms, whereas α 2 -adrenoceptors, opioids and GABA deactivates the inhibitory mechanisms (Edwards and Johnson, 1991;Callera et al, 1993;Menani et al, 1996;Menani et al, 1998a;Menani et al, 1998b;Johnson, 1998, Andrade et al, 2004;Callera et al, 2005b;De Castro e Silva et al, 2006;de Oliveira et al, 2007;De Oliveira et al, 2008;De Oliveira et al, 2011;Menani et al, 2014;Andrade et al, 2015;Gasparini et al, 2015b;Pavan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%